LACONISS: A land consolidation integrated support system for planning and decision making - Demetriou, Demetris (My University, 2013)
This paper presents an Integrated Planning and Decision Support System (IPDSS) for land consolidation called LACONISS that integrates artificial intelligence techniques, namely expert systems and genetic algorithms, with multi-criteria decision making methods and a geographical information system. The system involves four modules: LandFragmentS for measuring land fragmentation in an agricultural context; a Land-SpaCES Design module for automating land redistribution; a LandSpaCES Evaluation module for assessing alternative land redistribution plans and; LandParcelS for automating land partitioning. The whole system has been applied to a case study area in Cyprus. The results have shown that LandFragmentS is more reliable than existing methods; the LandSpaCES Design module can successfully emulate planners' reasoning and rapidly produce alternative land redistribution plans; the LandSpaCES Evaluation module is a flexible tool for identifying the most beneficial plan; and LandParcelS produces realistic results. The contribution of LACONISS is relevant to both planners and landowners as it transforms land reallocation into a systematic, automated, transparent and efficient process that may alleviate current problems associated with this process. Eventually, LACONISS may constitute the foundations for developing a generic system that could be applied in any country that implements land consolidation plans.
Keywords: Expert systems; Genetic algorithms; GIS; Land consolidation; Land reallocation; Multi-criteria decision methods